Popiół i szarość - pamięć koloru, Jacques Derrida i Anselm Kiefer - Leśniak, Andrzej (Przestrzenie Teorii, 2007)
The imaginary landscapes of Anselm Kiefer and Jacques Derrida intersect at a very specific point. The motif of grey is present both in the painting activity of the German artist and in the textual body of the French theoretician. I have attempted here to analyse some particular images and a few fragments of text in order to show the importance and the function of grey in contemporary culture. The colour I deal with is unusual as it refers to some of the most pertinent topics of our history and art. The grey - both in the works of Kiefer and in the booklet of Derrida entitled Feu la cendre - is the trace of destruction, the sign of perishing and the colour of ashes. It is impossible to discuss the history of the 20th century without this very specific reference which is both visual and conceptual.